PAI Teachers' Strategies In Improving Students' Learning Activity In PAI Subjects In Elementary Schools (Case Study Research at SDN 2 Parakan Garokgek, Purwakarta Regency) - Nina Latipah Nur; Hisny Fajrussalam; Nurdiansyah (Penerbit Hellow Pustaka, 2024)
This study was motivated by observations showing low interest and activeness of students in participating in Islamic Religious Education (PAI) learning, which has implications for the achievement of learning objectives that are not optimal. This study explores the strategies Islamic Religious Education (PAI) teachers to improve student learning activeness in Elementary Schools. This study uses a qualitative approach with a case study method—data collection techniques through observation, interviews, and documentation studies. Research participants consisted of Islamic Religious Education (PAI) teachers, principals, and homeroom teachers at the school. Data analysis was carried out descriptively and qualitatively to understand the strategies applied by teachers in planning and implementing learning and the factors that influence its success. The study results showed that Islamic Religious Education (PAI) teachers used various innovative and creative learning strategies to improve student learning activeness, such as discussion methods, group work, and interactive learning media. In addition, this study identified factors that influence the success of learning strategies, including active student involvement, support from the school environment, and teacher competence and creativity in teaching. This study provides theoretical contributions in the form of new knowledge and insights regarding Islamic Religious Education learning strategies in elementary schools and practical benefits for teachers, schools, and educational institutions to improve the quality of learning and student learning activity.